Revelation : A Pentecostal Commentary - Skaggs, Rebecca,; Benham, Priscilla, (Pentecostal Commentary Series, 2009)
Where do we go after death? What happens to us? What factors influence our destiny? What will happen to the world in years to come? Is there a controlling divine force in human experience? Is there a plan, or is life a product of random occurrences, of chance? Why is it the righteous who are persecuted and suffer while the wicked seem to prosper? Is there justice in the universe? The book of Revelation offers answers to many of these questions. Since, however, it is one of the more difficult of the New Testament books to read and interpret, it is often overlooked, neglected or even avoided by today's Christians. Yet it addresses many prophetic issues of importance to those seeking to understand God's plan for the future. Speaking through its heavy symbolism and sometimes strange visions of heaven, angels, beasts, earthly turmoil and destruction, the Apocalypse offers hope that God will overcome evil and that he does indeed control human destiny.